The Value of Methodological Deductivism in Argument Construction - Shecaira, Fábio Perin (Informal Logic)

(untitled) (Informal Logic, 2018)
“Deductivism” is a broad label for various theories that emphasize the importance of deductive argument in contexts of rational discussion. This paper makes a case for a very specific form of deductivism. The paper highlights the dialectical importance of advancing deductively valid arguments (with plausible premises) in natural-language reasoning. Sections 2 and 3 explain the various forms that deductivism has taken. Section 4 makes a case for a particular form of deductivism. Section 5 discusses the value of deductive argument in law. Section 6 concludes and acknowledges critical questions that need to be addressed more fully in future work.